A localized lagrange multipliers approach for the problem of vehicle-bridge-interaction. (1st August 2018) - Zeng, Qing; Stoura, Charikleia D.; Dimitrakopoulos, Elias G.
Highlights: An accurate and efficient algorithm for vehicle-bridge-interaction problems. A partitioned and non-iterative time integration scheme for VBI problems. Artificial contact points enable the partition of the vehicle-bridge system. Contact forces are treated as localized Lagrange multipliers. Abstract: This paper proposes a time-integration analysis scheme for the vehicle-bridge-interaction problem. Key feature is the introduction of artificial auxiliary contact points between the wheels and the bridge deck elements in contact. The artificial points allow the formulation of two sets of kinematic constraints and two sets of contact forces (i.e. localized Lagrange multipliers), between the vehicle and the bridge, that enable the partitioned, non-iterative, dynamic analysis of the two subsystems. To demonstrate the accuracy of the proposed approach, the paper first examines a simple example of a single sprung-mass model traversing a simply supported bridge. Then, it considers a more realistic problem of eight train vehicles crossing an arch bridge. The train vehicles are simulated as multibody assemblies and the bridge with a three-dimensional finite element model. The results prove the computational efficiency of the proposed scheme compared to existing algorithms.